Effect of Deformation Temperature, Strain Rate and Strain on the Strain Hardening Exponent of Copper/Aluminum Laminated Composites. Issue 4 (July 2018) - Liu, Shuaiyang; Wang, Aiqin; Xie, Jingpei
In order to investigate the strain hardening behaviour of Cu/Al laminated composites, isothermal compression tests were conducted in the temperature range of 300–450 °C and stain rate range of 0.01–1 s −1 . Based on the experimental data, stain hardening exponent n was calculated to evaluate the strain hardening ability of Cu/Al laminated composites during the deformation process. The results show that deformation temperature, strain rate, strain and laminated structure are all responsible for the evolution of flow stress during the isothermal compression. The highly non-linear character of Ln σ - Ln ε curves shows the dynamic competition between work hardening and dynamic softening, and dynamic softening gradually plays a dominant role with the increase of strain. Furthermore, strain hardening exponent n is more sensitive to deformation temperature than strain rate. Lower deformation temperature and higher strain rate contribute to the enhancement of strain hardening exponent n.